ANALISIS PENGGUNAAN KALIMAT IMPERATIF DALAM TERJEMAHAN QS. 2 (AL-BAQARAH) - Junadi, Syafi’; maqruf (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to describe the forms of use and types of imperative sentences found in QS translations. 2 (Al-Baqarah). This type of research is descriptive qualitative. The qualitative descriptive method is research based on the philosophy of postpositivism, which is used to research the conditions of natural objects, where the researcher is the key instrument, data collection techniques are carried out by triangulation (combination). Data collection was carried out using the observation method through note-taking techniques. The research results show that the use of imperative sentences found in the translation of QS. 2 (Al-Baqarah) in this study amounted to 100 data, including: (1) Ordinary imperative sentences totaling 16 sentences, (2) Soft imperative sentences totaling 56 sentences, (3) Request sentences totaling 4 sentences, (4) Sentences The prohibition totals 23 sentences. Conclusion from the analysis of imperative sentences in QS translation. 2 (Al-Baqarah) shows that soft imperative sentences are dominantly used more often than ordinary imperative sentences, request sentences, and prohibition sentences found in QS translations. 2 (Al-Baqarah), because most of the sentences used in the QS translation. 2 (Al-Baqarah) is a subtle imperative sentence.